Comparison of three radiodiagnostic techniques for pyrophosphate arthropathy - Fatima Magomedovna Kudayeva; V G Barskova; A V Smirnov; L A Bozhyeva; R A Osipyants (Научно-практическая ревматология)
Pyrophosphate arthropathy (PPA) is a disease that arises due to the formation and deposition of calcium pyrophosphate crystals within the articular cartilage and thereby develops into immune inflammation. Its diagnosis requires the detection of characteristic calcium pyrophosphate crystals in the synovial fluid from the affected joint, as well as the signs of cartilage calcification or chondrocalcinosis visible on conventional X-ray films. The paper considers reasons why it is difficult to visualize chondrocalcinosis by knee joint radiography and compares the importance of three techniques for the radiodiagnosis of chondrocalcinosis as one of the important criteria for diagnosing PPA.